A comparative study of the philosophers of legal argumentation and soccer coaches - Goicochea Elías, José Julio (2022)
In the conviction that the law is like life itself and that of all the unimportant things, soccer is the most important, this article tries to find similarities and differences between the thinking of the referents of legal argumentation and that of football coaches who have left their mark on the sport. In the case of law, positions that proclaim weighting are reviewed, as well as one that defends it as a hard core; As far as soccer is concerned, ideas will be analyzed that despite the time that has elapsed remain valid and exalt their creators.